A Touch of Dead : Sookie Stackhouse : The Complete Stories - Harris, Charlaine (New York : Ace Books, 2009)
A collection of every short story featuring Sookie Stackhouse, the telepathic waitress heroine of the "Southern Vampire" novels, includes "Fairy Dust," "One Word Answer," and "Dracula Night."
Fairy dust -- Dracula night -- Word answer -- Lucky -- Gift wrap.
Keywords: Vampires -- Fiction; Short stories; Fiction